Formulation Of Palm Oil-Based Synthetic Lubricant As Hydraulic Fluid - Alias, Nor Halaliza (2007)
Increasing attention to the environmental issues drives the lubricant industry to choose the vegetable-based lubricants which are biodegradable compared to mineral-based fluids. Hydraulic fluids represent one of the most important groups of industrial lubricants, being widely used in industrial hydraulic systems, particularly for machine tools, steering gears, etc. However, the inherent properties of vegetable oil such as poor oxidative stability and high pour point have hindered its use. In this study, trimethlolpropane (TMP) ester, which is derived from palm based methyl ester (POME), was used as the base fluid. The purpose of this study is to determine the optimum formulation for palm oil-based synthetic lubricant as hydraulic fluid by using suitable additives that can improve the lubricating properties in accordance to the standard regulations.To determine the range of operating temperature suitable for hydraulic fluid purposes, the test was conducted using bench test. Two types of antioxidant additives, Additive A and Additive B were used at temperature ranged from 80°C, 90°C, 95°C and 100°C. The effects of additives on degradation of oil at these temperatures were determined based on the tests done at 0 hour, 24 hours, 48 hours, 72 hours, 96 hours, 200 hours, 400 hours, 600 hours and 800 hours. The oxidative stability of oil was evaluated based on the determination of the Total Acid Number (TAN) and viscosity tests. In general, the unadditived based-oil began to degrade after 200 hours. However, the additived oil was quite stable even after 800 hours of operation. The best formulation was obtained at 95°C by using 1.5% of Additive A. Two effects have been studied in this research, i.e. the effect of temperatures and also the effect of additives on TAN and viscosity value. Both TAN and viscosity value increased with heating temperature. Meanwhile, the results have proven that Additive A performs better compared to Additive B, based on the TAN and viscosity results. The final TAN value for additived oil was only 0.54 mg KOH/g as compared to 7.46 mg KOH/g for unadditived oil. Other lubrication properties such as kinematic viscosity and viscosity index were also studied. After 800 hours of operation, the final kinematic viscosity of the oil at 40°C and 100°C were 38.67 mm2/s and 7.9 mm2/s, respectively, as compared to 86.02 mm2/s and 13.5 mm2/s for unadditived oil. Meanwhile, the viscosity index (VI) was almost unchanged at 185. The standard working temperature used in the lab scale hydraulic test rig was 60°C. The maximum pressure 910 psi was able to push up the 20 kg load throughout the system,while the minimum pressure was maintained at 240 psi after the load was being pulled down. As the hydraulic cylinder moves up and down, the oil experienced shear stress ranged between 1 rpm to 2500 rpm. At 0 hour, the TAN value, kinematic viscosity of the oil at 40°C and 100°C were 0.22 mg KOH/g, 35.8 mm2/s and 7.5 mm2/s, respectively. Meanwhile, after 800 hours operation, the final TAN value was 0.65 mg KOH/g, whereas the final kinematic viscosity of the oil at 40°C and 100°C were 24.7 mm2/s and 6.3 mm2/s, respectively. The VI values ranged between 185 up to 221. Other tests on the formulated hydraulic fluid were also conducted, such as wear and friction, pour point, thermal stability by using TGA-DTA and filterability. These tests are important to ensure that this formulated hydraulic fluid confirm to the standard regulations. The pour point of the formulated oil was recorded at 10°C. Whereas, the wear scar diameter (WSD) in wear and friction tests were 1.0 mm under 15kg load and 3.24 mm under 40kg load. Both readings were recorded at 0 hour. Filterability test shows that some particles were produced in the hydraulic system after 800 hours operation due to the wear and tear. However, the amount of particles before (at 0 hour) and after the operation (at 800 hours) were only 0.32 g and 0.65 g, respectively.